Colorectal Cancer in Young Patient: A Distinguished Disease Entity? - Siti Nurdjanah; Suryo Taroeno; Putut Bayupurnama; Sutanto Maduseno; Neneng Ratnasari (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2005)
Background: Some studies suggested that colorectal cancer at young age had a distinct biological characteristic: more advanced stage at time of diagnosis, poorer differentiated, and consisted of large proportion of mucin producing tumors. Aim of the study: To analyze clinical and histopathological differences between young aged colorectal cancer patients ( 40 years old) and the older patients Methods: A cross-sectional retrospective study was conducted among our colorectal cancer patients in a general hospital between 1999-2004, using C.18, C.19, C20 ICD X code in medical record searching. It was requested that the patients had surgical treatment in Dr. Sardjito General Hospital. An inconclusive clinical staging and/or histological data were among the exclusion criteria. Chi-square, Fisher’s exact test, T-test, and Mann Whitney U-test was performed to analyze the difference between patients 40 years old and ³ 40 years old, in respect to diagnostic staging, histological type, histological grade (differentiation), CEA level, hemoglobin, albumin, tumor location, and chief complain. With p 0.05 was considered as significant. Results: Sixteen young aged ( 40 years old) and 72 older patients had been identified. No differences in gender proportion and mean of symptoms to diagnosis period between two groups. No statistical differences between young aged and the older patients in diagnostic staging, histological grade and type, CEA level, and hemoglobin. Young aged patients had higher albumin value at presentation (p = 0.014), all had left sided tumors (p = 0.035), more complain of anal pain (p 0.001), and less change of bowel habits complain (p = 0.009) Conclusion: The study results had failed to confirm the difference in respect to diagnostic staging, histological type and grade, CEA level, and hemoglobin. Most of our young aged patients had left sided tumors with chief complain of anal pain, and less complain of change of bowel habits Keywords: Young aged colorectal cancer patients, cross sectional analysis, clinical and histological difference